3D printed porous PEEK created via fused filament fabrication for osteoconductive orthopaedic surfaces. (September 2020) - Spece, H.; Yu, T.; Law, A.W.; Marcolongo, M.; Kurtz, S.M.
Abstract: Due to its unique and advantageous material properties, polyetheretherketone (PEEK) is an attractive biomaterial for implantable devices. Though concerns exist regarding PEEK for orthopaedic implants due to its bioinertness, the creation of porous networks has shown promising results for interaction with surrounding tissue. In this study, we created porous PEEK via clinically-available fused filament fabrication (FFF, 3D printing) and assessed the pore structure morphology, mechanical properties, and biologic response. The designs of the porous structures were based on a simple rectilinear pattern as well as triply periodic minimal surfaces (TPMS), specifically gyroid and diamond types. The material characteristics, including porosity, yield strength, and roughness, were evaluated using μCT, static compression testing, and optical profilometry. The porous PEEK, along with 3D printed solid PEEK, was then seeded with MC3T3-E1 preosteoblast cells for evaluation of cell proliferation and alkaline phosphatase (ALP) activity. The samples were then imaged via scanning electron microscopy (SEM) to observe cell morphology. μCT imaging showed the porous networks to be open and interconnected, with porous sizes similar (p > 0.05) to the as-designed size of 600 μm. Average compressive properties ranged from 210 to 268 MPa for elastic modulus and 6.6–17.1 MPa for yield strength, with strength being greatest for TPMS constructs. SEM imaging revealed cells attaching to and bridging micro-topological features of the porous constructs, and cell activity was significantly greater for the porous PEEK compared to solid at multiple time points. Graphical abstract: Image 1